Effects of sustained i.c.v. infusion of lupus CSF and autoantibodies on behavioral phenotype and neuronal calcium signaling - Minesh Kapadia; Dunja Bijelić; Hui Zhao; Donglai Ma; Ljudmila Stojanovich; Milena Milošević; Pavle Andjus; Boris Šakić (Acta Neuropathologica Communications, 2017)
Abstract Systemic lupus erythematosus (SLE) is a potentially fatal autoimmune disease that is often accompanied by brain atrophy and diverse neuropsychiatric manifestations of unknown origin. More recently, it was observed that cerebrospinal fluid (CSF) from patients and lupus-prone mice can be neurotoxic and that acute administration of specific brain-reactive autoantibodies (BRAs) can induce deficits in isolated behavioral tasks. Given the chronic and complex nature of CNS SLE, the current study examines broad behavioral performance and neuronal Ca2+ signaling in mice receiving a sustained infusion of cerebrospinal fluid (CSF) from CNS SLE patients and putative BRAs (anti-NR2A, anti-ribosomal P, and anti-α-tubulin). A 2-week intracerebroventricular (i.c.v.) infusion of CSF altered home-cage behavior and induced olfactory dysfunction, excessive immobility in the forced swim test, and perseveration in a learning task. Conversely, sustained administration of purified BRAs produced relatively mild, both inhibitory and stimulatory effects on olfaction, spatial learning/memory, and home-cage behavior. In vitro studies revealed that administration of some CSF samples induces a rapid influx of extracellular Ca2+ into murine neurons, an effect that could be partially mimicked with the commercial anti-NR2A antibody and blocked with selective N-methyl-D-aspartate ﻿(NMDA) receptor antagonists. The current findings confirm that the CSF from CNS SLE patients can be neuroactive and support the hypothesis that intrathecal BRAs induce synergistically diverse effects on all domains of behavior. In addition, anti-NMDA receptor antibodies may alter Ca2+ homeostasis of central neurons, thus accounting for excitotoxicity and contributing to the heterogeneity of psychiatric manifestations in CNS SLE and other autoantibody-related brain disorders.